Murtaza Mutahhari: Bridging Tradition and Modernity in Islamic Education Philosophy - Mir, Khalid Hussain; Anjum, Rafique (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study investigates the significance of Ayatullah Murtaza Mutahhari's educational philosophy amidst the challenges faced by contemporary Muslim societies. The study's main objectives are to scrutinize the core principles of Mutahhari's educational philosophy, evaluate its institutional and curricular consequences in post-revolutionary Iran, and discover practical implications for educational reform in contemporary Muslim societies. Using a qualitative approach, the study delineates Mutahhari's and relevant scholarly works to discover the integration of revelation, rationality, and ethical construction within the framework of his educational philosophy. The study's findings reveal that Mutahhari's thoughts advocate a holistic approach to education that underscores spiritual growth and critical thinking, critiques materialist principles, and fosters women's education. The implications of this study go beyond academic discourse by providing insights to educators, scholars, and policymakers on the reform of educational objectives and methods. Ultimately, the study affirms that Mutahhari's thoughts can conform to a meaningful, ethical, and trustworthy education framework and contribute to a more comprehensive discourse on Islamic intellectual revitalization.